Impact of copper doping in NiO thin films on their structure, morphology, and antibacterial activity against Escherichia Coli. Issue 4 (March 2020) - Aftab, Muzamil; Butt, M.Z.; Ali, Dilawar; Bashir, Farooq; Aftab, Z.H.
Abstract: Impact of Cu doping on the structure, morphology, and antibacterial activity of NiO thin films has been investigated for a broad range of Cu/Ni ratios (0.1–25%). These thin films were synthesized on pre-heated glass substrates using indigenous spray pyrolysis setup. The structural analysis via X-ray diffraction technique reveals that all the thin films are of polycrystalline nature with cubic structure. All the diffraction peaks shift towards lower angle on an increase in the Cu/Ni ratio. Texture coefficient and stacking fault probability were determined by Harris analysis and Warren – Warekois formula, respectively. Crystallite size and lattice strain were valued by means of Williamson – Hall analysis, size-strain plots, Scherer and Wilson formulae. The value of crystallite size shows a decreasing trend while lattice strain increases on increasing the Cu/Ni ratio. SEM micrographs of the thin films reveal that surface morphology consists of pores, and the density of these pores decreases as the Cu/Ni ratio increases. The characteristic absorption bands exhibited by FTIR spectra of un-doped NiO and NiO:Cu thin films recorded in the range 4000–450 cm −1 were identified. Pure NiO thin film is found to be a very good antibacterial agent against the Escherichia Coli bacteria. However, its antibacterial ability gradually decreases on doping with 0.1–25% Cu.